A CASE HISTORY ON THE PHENOMENAL CORROSION OF MARINE PROPELLERS IN FISHING BOATS - BALASUBRAMANYAN, R (Fishery Technology, 2016)
Although high tensile brassess of copper-zinc alloys (Manganese bronze) find extensive use in all marine applications, under aggressive sea-water, marine propellers cast out of such an alloy frequently suffer heavy corrosion damages due to dezincification. An interesting case history where a number of propellers have undergone dezincification in the Cochin back-waters is narrated in this paper.